Development of Broadly Applicable Reference EVs Expressing Horseradish Peroxidase - Daniela Waas; Marc Juraschitz; Yen‐Fu Adam Chen; Harald Waltenberger; Wolfgang Hammerschmidt; Reinhard Zeidler; Sonja Molinaro; Kathrin Gärtner (Journal of Extracellular Vesicles)
ABSTRACT Extracellular vesicles (EVs) hold great promise as circulating biomarkers for diagnostic and therapeutic approaches. Thus, many research groups world‐wide investigate important aspects of EVs including their biology and medical significance. For this, a large number of procedures and protocols has been established making it difficult to almost impossible to compare and replicate results. Consequently, diagnostic tests remain problematic to interpret, mainly because the use of reliable reference EVs as a qualified standard has not yet gained widespread acceptance. Beyond doubt, such reference EVs are key to assess EV preparations quantitatively and to establish robust quality control processes to ensure overall quality and validity of data. To further advance the establishment of such controls, we designed and generated a new class of reference EVs expressing horseradish peroxidase (HRP) to facilitate simple and reliable EV tracing during isolation and standardization of EV purification and downstream analysis processes. HRP+ EVs can be quantified easily and with unmatched sensitivity either directly via measuring HRP activity or indirectly via immunodetection of HRP on the EV surface. We demonstrate that HRP+ EVs allow the reliable quantification of absolute EV numbers in biological or medical samples to normalize clinical specimens in liquid biopsies.